Educational short film versus powerpoint based lecture in school tobacco awareness programs: Study from a tertiary cancer Center, Kerala, India - Neethu Ambali Parambil; Phinse Mappalakayil Philip; Satheesan Balasubramanian; Maya Padmanabhan (Wolters Kluwer Medknow Publications, 2022)
Multimedia, being more attention-getting and attention-holding, is a powerful tool for mass awareness creation and is used for intervention among students in many studies. Our aim was to see the effectiveness of an educational short film in tobacco awareness generation and to compare it with the traditional lecture-based awareness. Selected schools were divided into two groups as per convenience. Short film was used as intervention in Group 1 and PowerPoint-based lecture in Group 2. The increase in awareness was assessed by a pre and posttest. On analysis, though both methods increased awareness as given by higher posttest score, it is found that the awareness levels showed a statistically significant difference between educational short film on hazards of tobacco and power point-based lecture using Mann-Whitney test. Our study proves that an educational short film carefully scripted and picturized can be used effectively in imparting awareness in school-based tobacco control programs.